Pengaruh Latihan Core Stability Terhadap Peningkatan Kesegaran Jasmani Pada Anak Usia 13-15 Tahun di Sekolah Sepak Bola Kalasan - Nugroho, Arif; , Maskun Pudjianto, SMPh., S.Pd., M.Kes (2017)
Backgrounds: 13-15 years of age is early adolescence. Where rapid changes, including physical development and motor skills. Physical fitness is the ability of a person doing the daily work efficiently without arising excessive fatigue so can still enjoy the spare time. The role of physiotherapy in improving physical fitness, especially in the field of footballs is by using core stability exercises. Objective: To know the influence of core stability exercises against the increase of physical fitness against children aged 13-15 years old at Kalasan soccer school. Methods: using a quasi experiment and two group pre and post test design. Research on sample 40 the respondents are divided into two groups. Group I as many as 20 respondents provided core stability exercises and group II 20 respondents were not given preferential treatment. Data analysis using test Willcoxon and Mann Whitnney test. Results: Group I provided core stability exercise obtained values p 0.5 and group II < value p < 0.5. While on test the difference value of p < 0.5. Conclusion:The existence of core stability exercise influence towards increasing physical fitness in children aged 13-15 years old at Kalasan soccer school. eywords: Physical fitness, Core Stability, Kalasan soccer school